Theoretical and experimental investigation of a novel high temperature heat pump system for recovering heat from refrigeration system. (25th August 2016) - Zhao, Zhaorui; Xing, Ziwen; Hou, Feng; Tian, Yafen; Jiang, Shaoming
Highlights: A novel heat recovery system in low temperature refrigeration system. Natural refrigerant ammonia is employed and analyzed. Specialized semi-empirical model for high pressure twin screw compressor. Experimental investigation on compressor and heat pump system performance. Abstract: Ammonia has been widely employed as the working media in industrial refrigeration systems including cold chain or pharmaceuticals industry. The condensers of such system are releasing large amount of heat especially in large capacity applications. On the other hand, heating supply at the temperature of 80 °C or even higher is also greatly demanded in related processing systems. High temperature heat pumps, which are capable of recovering heat from condensers of refrigeration systems, could be much more highly efficient compared to boilers or electric heaters. Conventional heat pumps employ heat exchangers on existing refrigeration system condenser, but have much drawback and less efficiency in practical applications. In this paper, a novel system employing higher temperature ammonia twin screw compressors is introduced and analyzed for recovering heat and supplying hot water. A new semi-empirical model is specially developed for high pressure twin screw compressors. Both theoretical and experimental investigations are conducted on such system, while validation of simulation accuracy and efficiency analysis of such system is also given.